Factors affecting the effectiveness of kindergarten management in Vietnam - Nhung, Chu Thi Hong; Hanh, Nguyen Thi Thu; Thi, Nho Hoang; Ngoc, Phuong Le; Thu, Hang Vu (Edelweiss Applied Science and Technology, 2026)
In the context of Vietnam’s educational reforms and the push for institutional autonomy, management effectiveness in early childhood education (ECE) has become a decisive factor in ensuring educational quality. This study examines the impact of five key predictors, leadership capacity, teacher professional quality, policy compliance, parental engagement, and resource adequacy, on the effectiveness of kindergarten management in Vietnam. Using a cross-sectional survey design, data were collected from 412 managers and teachers across public and private sectors. The results from multiple linear regression analysis indicate that the model is statistically significant and explains [62.4%] of the variance in management effectiveness (R^2 = 0.624, adjusted R^2 = 0.618, p < .001). Leadership capacity and teacher quality emerged as the strongest predictors (beta = 0.42 and beta = 0.35, respectively, p < .001), while policy compliance and parental engagement showed moderate but significant effects. The findings highlight systemic challenges such as policy fragmentation and workload pressure. This study provides a theoretical framework for ECE governance and offers practical implications for policymakers and school administrators to enhance accountability and educational outcomes in the Vietnamese context.